Perilaku Arsitektur & Pola Ruang Pada Pengrajin Gerabah di Desa Negara Ratu, Natar, Lampung Selatan - Vannia Salma Salsabila; Yunita Kesuma (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2021)
Pottery is a work of art made with clay as raw material and then dried and burned. Pottery works are thought to have existed since pre-historic times, precisely when humans began to live sedentary lives and cultivate crops. Archaeology in Indonesia has found many pottery works that functioned as home utensils or religious purposes used for ceremonies and burials. Over time, craftsmen began to develop new and more modern designs and creations. Community empowerment is part of a social welfare strategy developed through Micro, Small, and Medium Enterprises (MSMEs) that improve people's living standards. The market interest in pottery products is shown by the potential that is utilized and developed in Negara Ratu Village, Sidoharjo Hamlet, South Lampung. Where in the area there are various kinds of pottery workshops or industrial houses that produce pottery products and trade them. Through this research, which uses analytical methods and direct surveys of building samples, it will be seen the architectural behavior and spatial patterns applied to each production house. So that the results of this study are a direction and conclusion on facilities and good spatial patterns that can be used based on architectural behavior patterns formed in buildings according to each user